All Days 2011
DOI: 10.2118/146998-ms
|View full text |Cite
|
Sign up to set email alerts
|

Improving Horizontal Completions on Heterogeneous Tight Shales

Abstract: Production from nanodarcy-range permeability shale formations requires extensive hydraulic fracturing, large volumes of water, and close-spaced wells. The current trend, which includes increasing lateral lengths, increasing the number of perforation stages, and increasing the volume of water and proppants pumped, is unsustainable. Comparing calculations of the possible surface area created during fracturing versus production results indicate that a large portion of the surface area is ineffective to production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Transversely isotropic elastic constants (Equation ) can be obtained from the engineering elastic parameters. It can be shown that the stiffness constants are given by Suarez‐Rivera et al: C11=Eh(1EhEvνv2)/AC33=Ev(1νh2)/AC44=2GvC13=Ehνv(νh+1)/AC12=Eh(EhEvνv2+νh)/A with A=false(1+νhfalse)false(12EhEvνv2νhfalse). …”
Section: Numerical Methods and Simulation Modelmentioning
confidence: 99%
“…Transversely isotropic elastic constants (Equation ) can be obtained from the engineering elastic parameters. It can be shown that the stiffness constants are given by Suarez‐Rivera et al: C11=Eh(1EhEvνv2)/AC33=Ev(1νh2)/AC44=2GvC13=Ehνv(νh+1)/AC12=Eh(EhEvνv2+νh)/A with A=false(1+νhfalse)false(12EhEvνv2νhfalse). …”
Section: Numerical Methods and Simulation Modelmentioning
confidence: 99%
“…If there is no horizontal stress contrast, or the maximum horizontal stress is in the same direction of the natural fracture's strike, hydraulic fractures will grow along the existing natural fracture orientation. Complex fracture networks will develop if there is a high horizontal stress contrast and the maximum horizontal stress is normal to the natural fracture strike (Suarez-Rivera et al 2013). Less brittle, soft shales aremore difficult to create large, conductive networks (Warpinski et al 2009).…”
Section: Modeling Fractured Mediamentioning
confidence: 99%
“…The mechanical properties for the TI rock are data published by Suarez-Rivera et al 23 We can assume an isotropic rock by using the mechanical properties measured in the x-direction of the TI rock as follows: E ¼44.68 GPa, v ¼ 0.283. Using the isotropic mechanical properties, one can calculate the isotropic linear elastic solution given by Jaeger et al 24 Figs.…”
Section: Linear Elasticitymentioning
confidence: 99%
“…The used data published by Suarez-Rivera et al 23 presented poroelastic example in Section 5 using the anisotropy ratios 1, 2 and 3. An anisotropy ratio of 1 corresponds to the isotropic rock model.…”
Section: Degree Of Anisotropy Effectmentioning
confidence: 99%
See 1 more Smart Citation